Technology Integration and Process Approach to Learning to Write Scientific Papers - Eliastuti, Maguna; Purwanto, Andri; Fidinillah, Mildan Arsdan; Herlina, Ninin; Karyati, Zetty; Irwansyah, Nur; Rabi Hamsah Tis'ah, J. Anhar; Ningsih, Retna (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Academic writing proficiency is fundamental for students, yet many faces significant challenges. This study synthesizes evidence on the effectiveness of technology integration, particularly AI, with the process approach in academic writing instruction. Method: Using systematic literature review following PRISMA guidelines, searches across eight databases yielded 85 articles (2010-2025) with inter-rater reliability Cohen's Kappa 0.78. Analysis employed thematic analysis using TPACK framework and SAMR model. Results: Reveal a significant research gap with only 9.4% of articles specifically integrating technology with process approach. Synthesis of 32 quantitative studies shows 87.5% report improved writing quality with medium-large effect sizes (d=0.45-1.20), particularly in language-grammar (93.3%), citation-referencing (100%), and structure-organization (89.3%). Affective aspects increased consistently: motivation (91.7%), self-efficacy (94.7%), and positive attitudes (95.2%). AI tools (25.9%) demonstrate high versatility supporting all writing process stages. Challenges include limited internet access (44.7%), lack of teacher training (49.4%), and infrastructure support (42.4%). Novelty: Includes integrated framework synthesizing multiple theories, evidence-based taxonomy of technologies for process writing stages, and contextualized analysis for Indonesia. Best practices emphasize purposeful integration, scaffolded implementation, critical engagement, and formative assessment.